A remarkable sensitivity enhancement in a gold nanoparticle-based lateral flow immunoassay for the detection of Escherichia coli O157:H71. Issue 56 (19th June 2015) - Cui, Xi; Huang, Youju; Wang, Jingyun; Zhang, Lei; Rong, Yun; Lai, Weihua; Chen, Tao
<x xml:space="preserve">Abstract</x> The size and uniformity of AuNPs were optimized to maximally amplify both visual inspection signals and quantitative data of LFA.